2023
DOI: 10.14569/ijacsa.2023.0140153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thermal and Electrical Conductivities on the Ablation Volume during Radiofrequency Ablation Process

Abstract: Radiofrequency ablation (RFA) is the treatment of choice for certain types of cancers, especially liver cancer. However, the main issue with RFA is that the larger the tumor volume, the longer the ablation period. That causes more pain for the patient, so the surgeons perform a larger number of ablation sessions or surgeries. The current commonly used electrode material, nickel-titanium alloy, used in RFA is characterized by low thermal and electrical conductivities. Using an electrode material with higher ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Consequently, an approximation treats the electromagnetic field as a quasistatic field. This approximation effectively describes the behavior using the Maxwell equations 34 :…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, an approximation treats the electromagnetic field as a quasistatic field. This approximation effectively describes the behavior using the Maxwell equations 34 :…”
Section: Governing Equationsmentioning
confidence: 99%
“…Their results indicated that the volume of ablation increases with materials having higher electrical and thermal conductivities, leading to a reduction in ablation time and consequently minimizing patient discomfort. Metals such as gold, silver, platinum, and nickel-titanium have suitable thermal and electrical conductivities 34 . Today, nickel-titanium is used in RF electrodes 35 .…”
Section: Introductionmentioning
confidence: 99%